Ekstraksi Ion Merkuri MenggunakanTeknik Emulsi Membran Cair dengan Variasi Konsentrasi Benzoil Aseton dalam Fasa Membran dan Variasi pH Fasa Eksternal - Sulniawati, Sulniawati; Hamzah, Baharuddin; Abram, Paulus Hengky (Universitas Tadulako, 2017)
Mercury ion extraction using the liquid membrane emulsion technique with the variation of benzoil aseton concentration in membrane phase and variation of pH of external phase has been done. The sample containing Hg2+ ions with a concentration of 20 mg/L. Variation of benzoil aseton were concentration of 0.01 M, 0.015 M, 0.02 M and 0.025 M, whereas variation of external phase pH used were 1,5; 2; 2,5; 3 and 3,5. The measurement of extraction was conducted by using UV-Vis spectrophotometer. The results showed that the largest percent extraction on the extraction of mercury ions in solution by using liquid membrane emulsion was at a concentration of benzoil aseton 0.02 M with the percentage of extraction 79.33% and the pH external phase 2 with the percentage of extraction 85.30%.